Wireless 3-Axis Accelerometer System for Measurement of Structural Displacement - Gürkan, Koray; Dindar, Ahmet Anıl; Akpınar, Burak; Gülal, Vahap Engin; GÜRKAN, GÜRAY (IEEE, 345 E 47Th St, New York, Ny 10017 Usa, 2013)
In this study, we present the design of a 3-axis acceleration measurement system that is capable of UTC (Coordinated Universal Time) time-stamping captured from a Global Positioning System (GPS) receiver module. With this achievement, the system is able to monitor and record the 3-axis vibrations with respect to an absolute time rather than the local sensor (and computer) time. Acquired 3-axis acceleration data and UTC are transferred via Bluetooth (R) protocol and developed software which enables monitoring and recording of UTC and acceleration data on a PC, respectively. For verification and synchronization quality test of acceleration data, shake-table tests were conducted for simulation of structural displacement and the calculated displacements were compared with a displacement sensor of a commercially available shake table system.
Keywords: GPS; acceleration measurement; accelerometers; Bluetooth; computerised monitoring; displacement measurement; Global Positioning System; protocols; sensors; synchronisation